AB0681 Bisphenol A Levels in Patients with Ankylosing Spondylitis and Its Correlation with Disease Activity. (10th June 2014) - Ustun, N.; Ustun, I.; Yagiz, A.E.; Okur, R.; Turhanoglu, A.D.; Sungur, S.; Gokce, C.
Abstract : Background: Ankylosing spondilitis (AS) is a systemic chronic inflammatory disorder of unidentified etiology. Bisphenol A (BPA) which act as a protective lining on the inside of metal-based food and beverage cans, is a chemical produced in large quantities for use primarily in the production of polycarbonate plastics such as hard plastic bottles and epoxy resins. BPA is an estrogenic endocrine disruptor that exerts an extensive variety of metabolic effects. Objectives: The objective of present study was to measure serum BPA levels in patients with AS and to explore a possible link between serum BPA levels and disease activity scores. Methods: A total of 50 AS patients (40 male, 10 female, mean age 41.14±11.65 years, mean body mass index 26.78±3.94 kg/m 2 ) and 30 age-sex- and body mass index-matched healthy controls (23 male, 7 female, mean age 41.44±6.98, mean body mass index 27±3.06 kg/m 2 ) were taken to the study. Disease activity of the AS patients was measured by Bath ankylosing spondylitis disease activity index (BASDAI). Results: The median disease duration of the AS patients was 10.68±10.43 years. Forty-three patients were taking NSAID and/or DMARD. Seven patients were taking an anti-TNF agent. Serum BPA levels of the patients with AS was significantly higher than that of healthy controls (3.98±2.35 vs. 0.49±0.29; p=0.001). There was significant positive correlation between the serum BPA levels and BASDAI scores (r=0.321, p=0.025). Conclusions: These data clearly show that serum BPA levels are significantly higher in patients with AS in comparison to age-sex-BMI-matched healthy controls. Furthermore, levels of BPA in AS patients were positively correlated with disease activity scores. References: Ozgocmen S, Akgul O, Altay Z, et al. Expert opinion and key recommendations for the physical therapy and rehabilitation of patients with ankylosing spondylitis. International journal of rheumatic diseases 2012;15(3):229-38. Vandenberg LN, Maffini MV, Sonnenschein C, Rubin BS, Soto AM. Bisphenol-A and the great divide: a review of controversies in the field of endocrine disruption. Endocrine reviews 2009;30(1):75-95. Rogers JA, Metz L, Yong VW. Review: Endocrine disrupting chemicals and immune responses: a focus on bisphenol-A and its potential mechanisms. Molecular immunology 2013;53(4):421-30. Wells EM, Jackson LW, Koontz MB. Association between bisphenol A and waist-to-height ratio among children: National Health and Nutrition Examination Survey, 2003-2010. Annals of epidemiology 2013. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1383